Analysis of the nutritional content of chicken feather fish meatballs as an alternative additional food for toddlers with undernut nutrition - Ferdina, Cucun Setya; Raharja, Kristian Triatmaja; Putri, Nindi Pramesthi Vardila; Fauziah, Nuraini; Pujiyani, Honesty (Institute of Computer Science (IOCS), 2024)
One of the nutritional problems that often occurs in Indonesia is malnutrition. Providing additional food is one of the nutritional supplements given as additional food or nutrients that are intended especially for malnourished toddlers. Chicken feather fish meatballs are one form of fishery product diversification that can be an alternative to providing additional food for malnourished toddlers. Based on the analysis of nutritional content, chicken feather fish meatballs have good nutritional content so that they can meet the nutritional needs required by the body, have a good impact on body health, at an affordable price and easy to obtain. Chicken feather fish meatballs have nutritional content including 13.01% protein content; 0.39% fat; 8.5% carbohydrates; 70.81% water content; and 2.9% ash content.